Experimental peri-implant mucositis around titanium and zirconia implants in comparison to a natural tooth: part 2-clinical and microbiological parameters - Clever, Kim; Schlegel, K. A.; Kniha, H.; Conrade, G.; Rink, Lothar; Modabber, A.; Hoelzle, F.; Kniha, Kristian (International Journal of Oral & Maxillofacial Implants, 2019)
The aim of this study was to assess the clinical and microbiological parameters around dental zirconia and titanium implants compared with natural teeth during experimental plaque accumulation. Clinical parameters were evaluated (gingival index, plaque index, bleeding on probing, and probing pocket depth). Microbiological samples were analyzed for total bacterial cell counts, as well as Tannerella forsythia and Prevotella intermedia counts. A statistically significant difference over time was observed in the groups in terms of the gingival index (P<0.001), plaque index (P<0.001), and bleeding on probing (P=0.039). The lowest mean total number of bacterial cells was measured around the teeth, followed by the zirconia implants; the highest values were found around the titanium implants. T. forsythia and P. intermedia values showed significant changes over time and sessions around the titanium implants. Compared to the soft tissues around zirconia implants and the teeth, those around titanium implants developed a stronger inflammatory response to experimental plaque accumulation in terms of the total number of bacterial cells and T. forsythia and P. intermedia values.
EVALuna2:206530